Diary in modern Ukrainian literature: varieties of the genre - Kulinska, Yanina I.; Koval, Olena I.; Redkina, Olga A.; Gerasimenko, Nina V. (Linguistics and Culture Review, 2021)
Diary literature was of interest to Ukrainian literary critics and literary critics from other countries in different years, but still most scientific studies occur in the mid-20th century. In Ukraine, the diary has been on the side-lines of the literary process for the past two decades. And only the turning points of historical events – the Revolution of Dignity and the Russian-Ukrainian war in eastern Ukraine – returned the genre to active public circulation: without exception, all the diaries of 2014-2020 were created during the crisis period, social upheavals. The relevance of the subject is explained by the need to use the latest practices to comprehend modern Ukrainian literature and, in particular, the diary genre as one of the components of modern military prose. The purpose of the study was to perform a thorough analysis of army diaries published during 2014-2020, study their genre nature, determine their distinctive features and create their general classification. Among the main methods for processing diary texts were historical-biographical, comparative historical, comparative, structural-narratological, interdisciplinary, as well as elements of hermeneutical, intertextual methods, text and discourse analysis, etc. The study presented a thorough analysis and suggested a new classification of the modern diary genre.